1996
DOI: 10.2172/251441
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium data for cesium ion exchange of Hanford CC and NCAW tank waste

Abstract: Reprint of hirtorical document TWRSPP-sZ-020. dated 1992. Data. formatting, and Mher mmntionr reflect stardards at the origiml date of printing. Tcchnieal peer reviews and editorial reviews may r a have teen performed. Laboratory (PNL) has studied several ion exchange materials f o r the recovery of cesium from Hanford waste tanks. tasks, 1) t o obtain equilibrium data f o r cesium ion exchange, and 2) t o evaluate ion exchange column performance. The subject of this l e t t e r report ' is the measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 1 publication
2
15
0
Order By: Relevance
“…This is a subset of the results displayed in Figure 3.1 and represents a range of data which are readily visible on the graph. The data profile is similar to that observed previously for cesium removal by ion exchange batch distribution tests from simulated and actual tank wastes (Bray et al 1992;Bray et al 1993a;Brown et al 199%;Brown et al 1996b;Kurath et al 1994). In general, for every material, the cesium K,, is nearly constant at low cesium concentration (e.g., less than 1 .OE-06 M Cs) but decreases at higher concentration (e.g., greater than 1.0505 M Cs).…”
Section: 2supporting
confidence: 87%
See 1 more Smart Citation
“…This is a subset of the results displayed in Figure 3.1 and represents a range of data which are readily visible on the graph. The data profile is similar to that observed previously for cesium removal by ion exchange batch distribution tests from simulated and actual tank wastes (Bray et al 1992;Bray et al 1993a;Brown et al 199%;Brown et al 1996b;Kurath et al 1994). In general, for every material, the cesium K,, is nearly constant at low cesium concentration (e.g., less than 1 .OE-06 M Cs) but decreases at higher concentration (e.g., greater than 1.0505 M Cs).…”
Section: 2supporting
confidence: 87%
“…CS-100 and resorcinol-formaldehyde (R-F) are two organic ion exchange resins that are commercially available and under consideration for cesium removal from Hanford tank wastes (Eager et al 1994;Kurath et al 1994;Orme 1995;Penwell et al 1994;Gallagher 1986@) CO), has been shown to exhibit a much greater loading for cesium and selectivity over sodium or potassium than the CS-100 resin (Bibler et al 1989;Bibler 1994;Bray et al 1990;Bray et al 1992;Bray et al 1993a;Brown et al 1995b;Kurath et al 1994). The chemical and radiation stability (Bibler 1991;Bibler and Crawford 1994;Brown et al 199%;Carlson et al 1995) and the structwe/function relationship (Hubler et al 1995;Hubler et al 1996a;Hubler et al 1996b) of the R-F resin to the ion exchange process have been studied extensively.…”
Section: 4mentioning
confidence: 99%
“…Experimental work completed from Fy 1992 through FY 1993 for cesium recovery included the determination of cesium batch distribution coefficients for three exchangers and two waste types (Bray et al 1992). the initiation of ion exchange column studies (Bray et al 1993), and radiation stability studies of the phenol formaldehyde resin CS-100 using 6OCo gamma irradiation (Bryan et al 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Complexant concentrate (CC) and NCAW were selected for the initid investigation (Bray et al 1992). Organic CC waste represents a high sodium waste containing organic complexants.…”
Section: Preparation Of Synthetic Wastesmentioning
confidence: 99%
“…The memos from Prignano (1989a and b) provided batch distribution information in NCAW and HN03 elution with Duolite CS-100, resorcinol formaldehyde (R-F), Duolite C-3, and ARC-359N in NCAW simulant. More recent work has focused on cesium sorption with IE-96, R-F, and CS-100 resins (Bray, et al 1992;Kurath et al 1994). Marsh, et al (1994a) has recently completed a comparison of resins in 101-SY simulant with CS-100, R-F, Ionsiv TIE-96 (IE-96 with titanium to improve Pu and Sr sorption), Durasil 230, and several other exchangers.…”
Section: Results Of Searchmentioning
confidence: 99%